Understanding the livelihoods of small-scale fisheries in Lamberts Bay : implications for the new small-scale fisheries policy - Nthane, Tsele Tommy (Department of Environmental and Geographical Science, 2015)
Small-scale fishers (SSFs) are among the most vulnerable socio-economic groups because of their high dependence on marine resource harvesting. While small-scale fisheries employ the overwhelming majority of the world's fishers and contribute substantially to the global catch, they are, on the whole, marginalised and ignored. Despite their importance in providing food security and livelihoods in coastal communities, state management authorities routinely neglect small-scale fisheries in favour of industrial fisheries. In South Africa, the exclusion of small-scale fishers is intricately linked with the oppressive policies of the apartheid government, which limited access to the fisheries for the largely Black and Coloured smallscale fishers. Changes within fisheries management practices led to the development of management tools that moved away from conventional resource-centred strategies, to management approaches that recognised the complexity of natural and ecological processes inherent within small-scale fisheries. Many of these new approaches have been embraced in South Africa's new small-scale fisheries policy. The policy represents a long line of arguably failed attempts at reforming South African fisheries undertaken by the South African government. While the policy is unique in the scale of participation by the small-scale fishers themselves it is still faced with the hurdle of implementation. The adoption of the individual rights approach embodied by the individual quota (IQ) system in the post-apartheid reforms has led to divisions within the community. Fishing rights benefited a small elite and disenfranchised many more fishers for whom fishing was a livelihood, but were excluded from the rights allocations. The new small-scale fisheries policy is widely acknowledged as progressive and carries the hope of inclusion for small-scale fishers along South Africa's coasts. After decades of disenfranchisement and individual rights allocations, the major challenge in the new policy's implementation will be dealing with the range of complex and unique communities in which the policy will be carried out. The purpose of this study was to establish a profile of the Lamberts Bay small-scale fisher groups and their perceptions regarding the new small-scale fisher policy, in order to inform the policy's implementation in Lamberts Bay.